Novel of water with (CeO2-WC) and (SiC-WC) nanoparticles systems for energy storage and release applications. Issue 3 (May 2019) - Hadi, Aseel; Rashid, Farhan Lafta; Hussein, Hasan Qahtan; Hashim, Ahmed
Abstract: The enhancements of heat transfer for water with different PCMs for solar energy storage and release have been investigated with high efficiency and high quality. The results revealed that the times of melting and solidification for release and storage of thermal energy decreases with an increase of the concentrations of (CeO2-WC) and (SiC-WC) nanoparticles. Also, the time of solidification and melting decreases with increasing of WC concentrations to water/CeO2 nanofluid and WC concentrations to water/SiC nanofluid.